Innovation Meets Tradition in the Sheep and Goat Dairy Industry - Caboni, Pierluigi; Scano, Paola (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
The domestic sheep (Ovis aries) and goat (Capra aegagrus hircus) are small ruminant species widely distributed throughout the world. They were among the first animals to be domesticated. Owing to their small stature and versatility, sheep and goats still are one of the most important food source in many arid regions. Traditionally, autochthonous breeds with a strong milk production seasonality were reared in extensive production systems, on a smallholder farming basis. The huge number and variety of their dairy products reflect the different cultures and traditions of vast areas of the world. However, today the traditional ovine and caprine dairy production chain, from farmers to exporters, is facing the challenges of innovation, sustainability, safety, and productivity, while at the same time protecting each product's individual characteristics. This Special Issue is dedicated to the field of ovine and caprine dairy production with ground-breaking perspectives and approaches, from physical-chemistry studies on milk and dairy, to new feeding strategies, herd management, nutritional quality, animal welfare, sustainability, and omics studies.